Предмет: Алгебра,
автор: LittleSlasher
Решите уравнение:
(х-2)^2=(х+3)^2
Ответы
Автор ответа:
0
(X-2)^2-(x+3)^2=0
(X-2-x-3)(x-2+x+3)=0
-6*(2x+1)=0
-12x-6=0
X=6/(-12)
X=-1/2
(X-2-x-3)(x-2+x+3)=0
-6*(2x+1)=0
-12x-6=0
X=6/(-12)
X=-1/2
Автор ответа:
0
1) Пусть выражения под степенью одного знака: х-2=х+3
Решений нет!
2) Если разного: х-2=-х-3
2х=-1
х=-0,5
Ответ: х=-0,5
Решений нет!
2) Если разного: х-2=-х-3
2х=-1
х=-0,5
Ответ: х=-0,5
Похожие вопросы
Предмет: Английский язык,
автор: ajymsmailova04
Предмет: Русский язык,
автор: ajglhasenova123
Предмет: Математика,
автор: Аноним
Предмет: Биология,
автор: MisterFrost
Предмет: География,
автор: ionela